قياس وتحليل التهرب الضريبي في مصر وتونس للمدة2018 - 2000 - هاشم محمد عبدالله العركوب,; سناء شامل محمد صالح, (PROSPECTIVE RESEARCHES, 2023)
The phenomenon of tax evasion is a global phenomenon that affects developing and developed countries, and there are strong indications that this phenomenon is constantly increasing, and that most countries are trying to control tax evasion, but the percentage of its severity varies from one country to another. There are indicators for evaluating the performance of the tax structure, which together represent the establishment of an optimal framework for the tax performance of the tax structure in a country for a limited period of time, and these indicators include the tax burden and tax energy The results of the assessment of the standard model showed that the actual tax burden index as a dependent variable affects it in a significant and inverse way, the ratio of the agricultural sector’s contribution to the GDP, and the variable of the mining sector’s ratio to the gross domestic product in a significant and inverse way. The results showed that there was no significant effect of the two variables, tax awareness and the percentage of industrial sector contribution This study is distinguished by the fact that it passed all the required standard work stages and solved all problems to reach the reality of the optimal tax burden (tax energy). Then the value of tax evasion was calculated, which represents the difference between the values of the optimal tax burden and the actual tax burden, and it is a first attempt at the level of contemporary studies. I was able to calculate the tax evasion values in a standardized manner.